Ministry of Trade and Industry Decree No. 9 For The Year 2022 = وزارة التجارة والصناعة قرار رقم 9 لسنة 2022 - The Middle East Library for Economic Services (The Middle East Library for Economic Services, 2025)
English & Arabic